2018
DOI: 10.29252/jhehp.4.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Can Educational Intervention be Useful in Improvement of Body Posture and Work Related Musculoskeletal Symptoms?

Abstract: The risk of WMSDs is higher in some professions considering the involved risk factors , presenting an important ergonomic issue [1,5]. WMSDs are the main health problems in industrial workers and ergonomists [6,7]. In Europe, WMSDs have been reported to affect 45 million employees [5]. These disorders may reduce productivity and quality, leading to economic and social consequences [8]. Therefore, adequate studies are required in order to prevent and decrease the risk of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To the best knowledge of the author, this is the first study that will evaluate the effects of theory-based educational intervention based on Bayesian model and fuzzy sets. On the other hand, other previous ergonomic interventions on the assembly-line workers have not used health education theories [ 41 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best knowledge of the author, this is the first study that will evaluate the effects of theory-based educational intervention based on Bayesian model and fuzzy sets. On the other hand, other previous ergonomic interventions on the assembly-line workers have not used health education theories [ 41 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Workplace hazards are of crucial importance, and various strategies have been implemented to prevent or minimize the probability of accidents. S&H training plays a key role in decreasing the rate of accidents, and inadequate training has been reported to be a major cause of accidents [11,25,27]. The findings of the current research demonstrated that some TFs could contribute to construction accidents, such as periodic training and duration and the contents of training.…”
Section: Feature Selectionmentioning
confidence: 62%
“…According to the World Health Organization (WHO, 2021), MSDs are a major contributor to the global burden of disease, affecting 1.71 billion persons worldwide. MSDs also affect 45 million workers within Europe (Samadi, Rostami, Bakhshi, Garosi & Kalantari, 2018). Musculoskeletal disorders constituted 44% of all work-related injuries and all disease-related costs in the workplace globally in 2019 (Moradi, Tavafian & Kazemi, 2022).…”
Section: Introductionmentioning
confidence: 99%